Recurrent pyogenic infections caused by a novel Gln1420* mutation in the C3 gene - Coelho, Pedro Simão; Gouveia, Catarina; Pinto, Marta Valente; Neves, Conceição; Cordeiro, Ana Isabel; Neves, João Farela (Frontiers in Pediatrics, 2022)
C3 is a crucial protein of the complement system. Congenital C3 deficiency is extremely rare and manifests through recurrent, severe infections and should always be considered as a differential diagnosis of recurrent pyogenic infections. We report a case of a patient with a novel C3 gene mutation, responsible for complete C3 deficiency with impaired complement system activation and recurrent infections.